Transatlantic Ties of the Far Right: The NSU Case in Germany and its Links to Actors and Incidents in the USA - Schultz, Tanjev (Terrorism and political violence, 2023)
The “National Socialist Underground” (NSU) is one of the most severe cases of terrorism in Germany after World War II. For more than twelve years, three neo-Nazis had lived under false identities in Germany. The group murdered ten people and committed several crimes. At first sight, this seems to be a case of domestic terrorism, but a closer look exposes transnational facets and turns it into an example of transatlantic ties between far-right groups. In their strategy and in their ideology, the German neo-Nazis and their circle of friends and supporters have been influenced by actors and incidents in the U.S. As the article shows, a powerful tradition of anti-Americanism in the milieu of Germany’s far right does not contradict an alliance of anti-Semites and white supremacists in both countries. Drawing on police files, intelligence reports, parliamentary hearings and court proceedings, the article lays out and analyzes the intertwining of German and U.S. militant right-wing actors. It examines references and connections to the Ku Klux Klan, “The Turner Diaries,” and to the U.S. terrorist group “The Order.”